Topical therapy for facial allergic dermatoses - Y. S. Kondratyeva; T. N. Shepileva; E. A. Subbotin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The research goal is to assess clinical dynamics and morphofunctional skin parameters of patients with facial allergic dermatoses on the background of combined topical therapy. Materials and methods. 45 patients with various facial allergic dermatoses in dry and sensitive skin took part in the research. The methods included anamnesis taking, poll, objective examination and assessment of morphofunctional parameters of skin, as well as estimation of life quality dynamic index (LQDI). Main results. After a course of treatment with 0,05% solution of alclometasone dipropionate inflammation of dermatosis ceased in 45 (100%) patients, itching and pains in 39 (86,7%) patients, but complaints about dryness and peeling of facial skin remained in 41 (91,1%) and 40 (88,8%) patients respectively. On the background of therapy including emollient Aflocream the above mentioned symptoms did not appear in 43 (95,6%) patients, wherein maximum effect was achieved in patients with allergic contact dermatitis - 14 (93,3%). After a course of topical therapy all patients showed statistically significant increase of epidermal moisture level, alongside with reduction of skin relief and degree of keratinization. During the assessment of LQDI a tendency to reduction of proportion of patients on whom the disease has a strong and extremely strong impact was noted in 10 patients (i.e. 22,2%), moderate influence - in 5 of them (11,45%), insignificant influence or its absence - in 30 (66,7%) people. Conclusion. Combined therapy including the use of a topical corticosteroid Afloderm and an emollient Aflocream showed good clinical efficiency in patients with facial allergic dermatoses. The efficiency is also confirmed with improvements in morphofunctional characteristics of patients' skin on the background of therapy.